The AU-rich element mRNA decay-promoting activity of BRF1 is regulated by mitogen-activated protein kinase-activated protein kinase 2 - Maitra, Sushmit (Cold Spring Harbor Laboratory Press, 2008)
Regulated mRNA decay is a highly important process for the tight control of gene expression. Inherently unstable mRNAs contain AU-rich elements (AREs) in the 3′ untranslated regions that direct rapid mRNA decay by interaction with decay-promoting ARE-binding proteins (ARE-BPs). The decay of ARE-containing mRNAs is regulated by signaling pathways that are believed to directly target ARE-BPs. Here, we show that BRF1 involved in ARE-mediated mRNA decay (AMD) is phosphorylated by MAPK-activated protein kinase 2 (MK2). In vitro kinase assays using different BRF1 fragments suggest that MK2 phosphorylates BRF1 at four distinct sites, S54, S92, S203, and an unidentified site at the C terminus. Coexpression of an active form of MK2 inhibits ARE mRNA decay activity of BRF1. MK2-mediated inhibition of BRF1 requires phosphorylation at S54, S92, and S203. Phosphorylation of BRF1 by MK2 does not appear to alter its ability to interact with AREs or to associate with mRNA decay enzymes. Thus, MK2 inhibits BRF1-dependent AMD through direct phosphorylation. Although the mechanism underlying this inhibition is still unclear, it appears to target BRF1-dependent AMD at a level downstream from RNA binding and the recruitment of mRNA decay enzymes.